Synergistic effects of TMC series nucleating agent and poly(ethylene glycol) on poly(lactic acid) based films: Mechanical, crystallization, storage, and optical properties - Xu, Shi; Hu, Ye; Shi, Yanming; Du, Baoyu; Zhang, Zhonggui; Gao, Hongyu; Li, Chengxue; Liu, Chunxiu; Nan, Huikai; Cheng, Jiafei; Dong, Yubing (International journal of biological macromolecules, 2025)
In this study, to overcome the limitations of insufficient toughness and heat resistance in polylactic acid (PLA), the poly(ethylene glycol)/PLA composite films were fabricated via melt blending and film blowing processes using PEG as a plasticizer, in combination with zinc phenylphosphonate, decanedioic acid, 1,10-bis(2-benzoylhydrazide), hexanedioic acid, and 1,6-bis(2-benzoylhydrazide) as nucleating agents. The objectives were to enhance the toughness, crystalline, and heat resistance properties, as well as to investigate the influence of nucleating agents and PEG on optical and storage characteristics. The results demonstrated PEG significantly improved ductility (elongation at break >300 %). The incorporation of the nucleating agent significantly enhanced the crystallization rate and elevated the glass transition temperature of the PEG/PLA composite films. Furthermore, the prepared PEG/PLA composite films exhibited good transparency (transmittance >75 %). The promoting mechanism of the by nucleating agents on the nucleation and crystallization of PLA has been systematically investigated. Storage tests revealed 15 wt% PEG minimized environmental impacts on film properties over five months and the performance of the composite films remained most stable in the refrigerator. 12 wt% and 18 wt% PEG exhibited an increase in yield strength while causing a decrease in elongation. This study provides valuable data for the development and the long-term storage of toughness PLA-based biodegradable packaging film materials.